Budaya Tallu Lolona Sebagai Dasar Beroikumene Semesta Bagi Masyarakat Toraja - Yenni Patrecia; Prayuda (Institut Agama Kristen Negeri Toraja, 2022)
God the Trinity, the creator of all things, which created everything in the world, allows creation to complement and unite itself, to realize things that are beneficial to God, that is, to maintain peace by building each other. In terms of issues related to the word ecumenical, the limited relationship between the different denominations–indirectly the relationship between humans outside the church with the natural environment, is not classed as ecumenical. This document invites the reader to understand the value of living the universal ecumenical call, reflecting upon the philosophy of Tallu Lolona, the analogy of God's creation that the sauan-sibarrung and sangserekan were given the gift of salvation must glorify God. Using qualitative descriptive methods and literary studies, this article interprets the gospel message of Tallu Lolona's philosophy (acts of love, unity, mutual cooperation, kinship, hard work, and peace/harmony); By failing to give an understanding of the limits of relationships among churches of different denominations, but rather harmonious relations with persons outside the walls of the church and all the creation of God in this world, as the incarnation of one in the household of God. Abstrak: Allah Trinitas Sang Pencipta segala sesuatu dalam dunia memberi kesempatan bagi seluruh ciptaan mengambil peran untuk saling melengkapi dan bersatu, mencapai hal yang dikehendaki Allah yakni memelihara damai sejahtera dengan saling membangun. Perihal kesatuan berkaitan dengan kata oikumene, dikenal sebatas relasi antara gereja dari berbagai denominasi yang berbeda–secara tidak langsung hubungan dengan manusia di luar gereja terlebih dengan alam sekitar, tidak tergolong dalam oikumene. Tulisan ini hendak mengarahkan pembaca untuk memahami bahwa patutlah menghidupi panggilan beroikumene semesta,, berkaca pada falsafah Tallu Lolona, analogi ciptaan Allah yang sauan-sibarrung dan sangserekan telah menerima anugerah keselamatan, harus memancarkan kemuliaan Allah. Dengan menggunakan metode kualitatif deskriptif dan studi pustaka, tulisan ini menginterpretasi pesan Injil Falsafah Tallu Lolona (tindakan kasih, persatuan, gotong-royong, kekeluargaan, kerja keras, dan kedamaian/kerukunan); dengan tidak memberi pengertian oikumene sebatas relasi antar gereja dari berbagai denominasi, melainkan relasi harmonis dengan orang-orang di luar tembok gereja dan seluruh ciptaan Allah di dunia ini, sebagai pengejawantahan satu dalam rumah tangga Allah.